Thermally activated delayed fluorescence emitters with a m, m-di-tert-butyl-carbazolyl benzoylpyridine core achieving extremely high blue electroluminescence efficiencies. Issue 11 (6th March 2017) - Rajamalli, Pachaiyappan; Thangaraji, Vasudevan; Senthilkumar, Natarajan; Ren-Wu, Chen-Cheng; Lin, Hao-Wu; Cheng, Chien-Hong
Abstract : High performance blue OLEDs with maximum EQEs over 28% are achieved from TADF emitters by fine tuning the acceptor unit. Abstract : Thermally activated delayed fluorescence (TADF) emitters are attractive for display and lighting applications. Here, a series of highly efficient blue TADF emitters including 3, 5-bis((3, 6-di- tert -butyl-9 H -carbazol-9-yl)phenyl)(pyridin-4-yl)methanone (4BPy- m DTC), (3, 5-bis(3, 6-di- tert -butyl-9 H -carbazol-9-yl)phenyl)(pyridin-3-yl)methanone (3BPy- m DTC), (3, 5-bis(3, 6-di- tert -butyl-9 H -carbazol-9-yl)phenyl)(pyridin-2-yl)methanone (2BPy- m DTC) and (3, 5-bis(3, 6-di- tert -butyl-9 H -carbazol-9-yl)phenyl)(phenyl)methanone (BP- m DTC) were designed and synthesized. The molecular structures feature two meta carbazole substituents attached to a benzoylpyridine (BPy) group or to a benzophenone (BP) group. These compounds show high thermal stability ( T d = 371–439 °C), blue emissions (458–488 nm), high photoluminescence quantum yields (PLQY) (75–96%) in thin films and very small energy gaps between S1 and T1 (Δ E ST ) of 0.01–0.05 eV. In addition, they all reveal TADF properties including small Δ E ST, two components in the transient PL decays, prompt emission and temperature-dependent delayed emission. The BPy series appears to give much higher photoluminescence quantum yields (PLQY > 92%) than BP- m DTC (75%) plausibly due to the more rigid structure caused by the interaction between pyridine nitrogen and the aromatic C–H bond. Furthermore, 4BPy- m DTC shows a more delayed component compared to 3BPy- m DTC and 2BPy- m DTC. The electroluminescent devices based on 4BPy- m DTC and 2BPy- m DTC as the dopant emitters exhibit sky blue emission with maximum external quantum efficiencies (EQEs) over 28%, and current and power efficiency and maximum luminance up to 67.0 cd A −1, 60.1 lm W −1 and 20 000 cd m −2, respectively. The presence of the pyridine ring and the position of the nitrogen atom in the molecules are critical for the high quantum yield and device efficiency. The PLQY EQE and luminance are dramatically improved by changing the phenyl into a pyridine group in the dopant in these devices.